Thermal cycling performances of multilayered yttria‐stabilized zirconia/gadolinium zirconate thermal barrier coatings. Issue 3 (20th November 2019) - Zhou, Dapeng; Mack, Daniel Emil; Bakan, Emine; Mauer, Georg; Sebold, Doris; Guillon, Olivier; Vaßen, Robert
Abstract: Gadolinium zirconate (Gd2 Zr2 O7, GZO) as an advanced thermal barrier coating (TBC) material, has lower thermal conductivity, better phase stability, sintering resistance, and calcium‐magnesium‐alumino‐silicates (CMAS) attack resistance than yttria‐stabilized zirconia (YSZ, 6‐8 wt%) at temperatures above 1200°C. However, the drawbacks of GZO, such as the low fracture toughness and the formation of deleterious interphases with thermally grown alumina have to be considered for the application as TBC. Using atmospheric plasma spraying (APS) and suspension plasma spraying (SPS), double‐layered YSZ/GZO TBCs, and triple‐layered YSZ/GZO TBCs were manufactured. In thermal cycling tests, both multilayered TBCs showed a significant longer lifetime than conventional single‐layered APS YSZ TBCs. The failure mechanism of TBCs in thermal cycling test was investigated. In addition, the CMAS attack resistance of both TBCs was also investigated in a modified burner rig facility. The triple‐layered TBCs had an extremely long lifetime under CMAS attack. The failure mechanism of TBCs under CMAS attack and the CMAS infiltration mechanism were investigated and discussed.